2015
DOI: 10.1155/2016/3190617
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System Control of Carbon Tetrachloride‐Induced Oxidative Stress in Liver through α‐Adrenergic Signaling

Abstract: In addition to being the primary organ involved in redox cycling, the liver is one of the most highly innervated tissues in mammals. The interaction between hepatocytes and sympathetic, parasympathetic, and peptidergic nerve fibers through a variety of neurotransmitters and signaling pathways is recognized as being important in the regulation of hepatocyte function, liver regeneration, and hepatic fibrosis. However, less is known regarding the role of the sympathetic nervous system (SNS) in modulating the hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It has been proven that the sympathetic nervous system participates in raising oxidative stress in the liver. Lin et al [19] have reported that hepatic oxidative stress induced by carbon tetrachloride injection was relieved in sympathectomized mice. Oben et al [20] have also reported that 6-hydroxydopamine, an agent used to induce chemical sympathectomy, significantly improved liver injury in mice with antioxidant-depleted diets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the sympathetic nervous system participates in raising oxidative stress in the liver. Lin et al [19] have reported that hepatic oxidative stress induced by carbon tetrachloride injection was relieved in sympathectomized mice. Oben et al [20] have also reported that 6-hydroxydopamine, an agent used to induce chemical sympathectomy, significantly improved liver injury in mice with antioxidant-depleted diets.…”
Section: Discussionmentioning
confidence: 99%
“…The use of β-AR blockers has been indicated to reduce oxidative stress in cardiac failure [ 31 , 32 ]. Chemical sympathectomy or α-AR antagonist treatment has profound inhibitory effects on CCl4-induced hepatic oxidative injury, which has important implications for understanding how the response to liver injury may be controlled [ 34 ]. Moreover, our results showed that the group infected with E. histolytica and treated with phentolamine increased HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is critical during the pathogenesis of CCl 4 -induced acute liver injury [27]. CCl 4 challenge produces highly reactive species and increases cellular production of ROS and MDA, leading to oxidative stress in tissues, especially the liver where it is primarily metabolized [6].…”
Section: Discussionmentioning
confidence: 99%